An Approach to Convert XMI Representation of UML 2.x Interaction Diagram into Control Flow Graph. (12th October 2011) - Kundu, Debasish; Samanta, Debasis; Mall, Rajib
Abstract : For automation of many software engineering tasks such as program analysis, testing, and coverage analysis, it is necessary to construct a control flow graph. With the advancement of UML, software practitioners advocate to construct control flow graph from some of the UML design artifacts. UML 2.x supports the modeling of control flow information in interaction diagram by means of message sequences and different types of fragments like alt, opt, break, loop, and so forth. Leading UML modeling tools, namely MagicDraw, IBM's Rational, and so forth export models in XMI format. Construction of control flow graph from the XMI representation of an interaction diagram is not straightforward as model elements of interaction diagram are captured in XMI by means of values of attributes of multiple tagged elements and correlations among these tagged elements is not explicitly specified. This paper proposes an approach for construction of control flow graph from XMI representation of UML 2.x interaction diagram. A prototype tool based on our approach has been developed which can be plugged in any computer-aided software engineering tool.